2018
DOI: 10.1093/aobpla/ply057
|View full text |Cite
|
Sign up to set email alerts
|

Do we truly understand pollination syndromes in Petunia as much as we suppose?

Abstract: Petunia is endemic to South America grasslands; member of this genus exhibit variation in flower colour and shape, attracting bees, hawkmoths or hummingbirds. This group of plants is thus an excellent model system for evolutionary studies of diversification associated with pollinator shifts. Our aims were to identify the legitimate pollinator of Petunia secreta, a rare and endemic species, and to assess the importance of floral traits in pollinator attraction in this Petunia species. To determine the legitimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 86 publications
1
31
0
Order By: Relevance
“…Although P. axillaris is primarily pollinated by hawkmoths, some bees and hummingbirds have been observed visiting its flowers (Lorenz-Lemke et al, 2006;Gübitz et al, 2009). P. exserta flowers display a set of traits usually seen in bird-pollinated species but share with P. axillaris some scent compounds that are attractive to bees (Rodrigues et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although P. axillaris is primarily pollinated by hawkmoths, some bees and hummingbirds have been observed visiting its flowers (Lorenz-Lemke et al, 2006;Gübitz et al, 2009). P. exserta flowers display a set of traits usually seen in bird-pollinated species but share with P. axillaris some scent compounds that are attractive to bees (Rodrigues et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it is important to note that, although color and bee visitation have been restored, P. secreta retains the typical long-tube floral morphology, which limits bee visitors to collecting pollen. Pollinator observations found that P. secreta attracts small halictid bees (Apoidea and Halictidae; as opposed to short-tube species' solitary bee pollinators of the Andrenidae and Colletidae), who indeed collect pollen rather than nectar [58].…”
Section: Discussionmentioning
confidence: 99%
“…These two Petunia species present suites of floral traits strongly related to their respective floral syndromes, hawkmoth in P. axillaris and hummingbirds in P. exserta (Stehmann et al 2009). No systematic pollination studies have been conducted in the field to identify which pollinators the intermediary colored plants attract and, except their pink shades that usually attract bees in Petunia species (Rodrigues et al 2018), other clues on pollinators remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, molecular characterization of genes and processes involved in floral syndromes shifts among Petunia species in general and P. axillaris and P. exserta species in particular (Amrad et al 2016;Sheehan et al 2016;Esfeld et al 2018;Rodrigues et al 2018), demonstrating the importance of a prezygotic barrier to reproductive isolation to maintain the species limits of this group. On the other hand, strong evidence of interspecific hybridization between P. axillaris and P. exserta was also obtained through molecular and morphological characterization, mostly at two sites in Guaritas (Turchetto et al 2019; LM Caballero-Villalobos unpubl.…”
Section: Introductionmentioning
confidence: 99%